Cálculos de Propriedades Eletrônicas e Magnéticas de ligas tipo Heusler Ni2MnGa1-xSnx (0 ≤ x ≤ 1) - Marcelo, Cesar Abraham Castañe da (2012)
Using Density Funcional Theory method, we performed a systematic study on structural, electronic and magnetic properties of the Ni2MnGa Heusler alloy when Gaatoms are gradually substituted by Sn. As main results, we observed that in the Ni2MnGa1-xSnx Heusler-type alloys (0 = x = 1), the Sn-substitution leads to a linear increase of the lattice parameter of the L21- type cell, which reduces its internal stress. The Sn-substitution also favors, on the one hand, an increasing of Mn-magnetic moments, but, on the other hand, it provokes a reduction of Ni-moments. These magnetic moment behaviors lead to a gradual reduction of the total magnetic moments of the Ni2MnGa1-xSnx Heusler-type alloys, in agreement with experimental observations that suggest a decreasing of the magnetization of the L21-phase with the increase of the Sn-content. Taking into account chemical disorders among Mn and Ga (or Sn) atoms in pure Ni2MnZ (Z = Ga or Sn) Heusler alloys, we determined the most favorable energetic spin configurations, when antiferromagnetic interactions are present in these alloys. In addition, we demonstrated that in the Ni2MnGa Heusler alloy, antiferromagnetic states are more energetically favorable than that in the Ni2MnSn compound; a result that may explain the existence of martensitic phase transformation in pure Ga- compound since these interactions are responsible for the structural transformation.